The Federalist papers - Hamilton, Alexander, 1757-1804; Madison, James, 1751-1836; Jay, John, 1745-1829; Goldman, Lawrence, 1957- (Oxford world's classics., 2008)
"The Federalist Papers comprise eighty-five essays written to persuade New Yorkers to ratify the Constitution of the United States in 1787-8. Written by key players in the American Revolution, they made a case for a new, united nation. They are the most important work of political thought to have come out of America." -- Provided by publisher.